2018
DOI: 10.1016/j.ijrobp.2017.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Interleukin (IL)4- and IL13-Mediated Phosphorylation of STAT6 (Tyr641) Decreases M2 Polarization of Macrophages and Protects Against Macrophage-Mediated Radioresistance of Inflammatory Breast Cancer

Abstract: These data suggest that inhibition of M2 polarization of macrophages by PM37 can prevent radioresistance of IBC by down-regulating PRKCZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 34 publications
3
74
0
1
Order By: Relevance
“…These findings demonstrated that the upregulation of PD-1 on ILC2s could enhance M2-like macrophage polarization from CD14 + monocytes by facilitating the production of IL-4 and IL-13. Our findings were in line with some previous reports that IL-4 and IL-13 could mediate M2 macrophage polarization in vitro (27,28).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings demonstrated that the upregulation of PD-1 on ILC2s could enhance M2-like macrophage polarization from CD14 + monocytes by facilitating the production of IL-4 and IL-13. Our findings were in line with some previous reports that IL-4 and IL-13 could mediate M2 macrophage polarization in vitro (27,28).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have demonstrated that IL-4 and IL-13, two canonical type 2 cytokines, could mediate M2 macrophage polarization (27,28). Considering the upregulation of IL-4 and IL-13 in PD-1 high ILC2s, we assessed the effect of ILC2 culture supernatant on the process of CD14 + monocyte polarization to M2-like macrophages in vitro.…”
Section: Pd1 High Ilc2s Enhance the Polarization Of M2-like Macrophagmentioning
confidence: 99%
“…It is possible that this may be reflecting an effect on macrophage M2 polarization. 39 Interestingly, IL-4 increased in the ipilimumab treated cohort and patients experiencing this increase had a better outcome. This increase has been observed in mice treated with ipilimumab but an association with outcome is not observed after ipilimumab monotherapy.…”
Section: Discussionmentioning
confidence: 94%
“…This alteration may change radio-sensitivity of the cancer cells. M1 macrophages enhance the radio-sensitivity of BC cells, but M2 macrophages trigger radio-resistance via IL-4/IL-13-mediated STAT6 phosphorylation and M2 polarization (132,133).…”
Section: Microbe-chemo Therapiesmentioning
confidence: 99%